Structural analysis of the choroid and the optic nerve in diabetes mellitus - Eylul Ercan, Zeynep (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the choroidal and peri-optic nerve head retinal nerve fiber layer (RNFL) changes in diabetes mellitus (DM) patients without retinopathy.Material and Methods: Four groups of 70 eyes were defined: control group (healthy subjects); group 1 - DM patients with glycated hemoglobin (HbA1c) level of 6.5–7.9%; group 2 (DM patients, HbA1c 8–9.5%); and group 3 (DM patients, HbA1c > 9.5%). Optical coherence tomography measurements of choroidal thickness (CT) and RNFL changes and were compared within groups.Results: CT was thinner in diabetic groups compared with control, but this decrease was not directly proportional to the HbA1c increase. CT loss in the subfovea was only seen in group 1. In temporal quadrant, all diabetic groups had RNFL loss compared with control, with no difference between them. RNFL in groups 2 and 3 had significant loss in the inferior temporal area compared with the control group, whereas in the inferior nasal quadrant, only group 3 had significant loss.Conclusion: CT changes were consistently seen in the lower HbA1c group compared with healthy subjects. This could be the result of the combined effect of low blood flow - which leads to CT decrease- that is then rivaled by the choroidal thickening due to increased vessel rigidity that is observed because of diabetic inflammation and high glycation end-product accumulation. RNFL was affected in temporal quadrants regardless to glycemic control. However, inferior RNFL damage was correlated with higher HbA1c levels, showing that optic nerve changes differ by diabetic control.
Keywords: Choroid; diabetes mellitus; glycated hemoglobin; OCT; optic nerve; RNFL